Preparation method of molybdenum matrix surface coating
By preparing the MoSi2 transition layer on the surface of the molybdenum matrix and forming (Mo, Cr, Ti)Si2 composite coating outside it, the problem of poor resistance to high-temperature oxidation performance of a single MoSi2 coating is solved, and the high-temperature oxidation life of the molybdenum matrix is significantly improved and antioxidant properties.
Patent Information
- Application Number
- CN202411442020.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2025-01-14
AI Technical Summary
Metal molybdenum is easily oxidized under a high-temperature oxidation atmosphere. The high-temperature oxidation resistance of a single MoSi2 coating is not ideal, and it is difficult to effectively block the diffusion of oxygen to the molybdenum matrix, resulting in insufficient oxidation life.
The MoSi2 transition layer is prepared on the surface of the molybdenum matrix, and then a (Mo, Cr, Ti)Si2 composite coating is formed outside the MoSi2 transition layer. By blocking or healing cracks, the diffusion resistance of oxygen is increased and the resistance to high-temperature oxidation is improved.
The high-temperature oxidation life of the molybdenum matrix is significantly improved, the mass change rate per unit area in the air at 1400℃ is reduced from -0.80% to +0.19%, and there is no oxidation and weight loss phenomenon in a short period of 1500℃, which significantly enhances the antioxidant performance.
Smart Images

Figure CN119307855A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of high-temperature anti-oxidation coating preparation, and in particular to a method for preparing a molybdenum substrate surface coating. Background Art
[0002] The statements herein merely provide background information related to the present application and do not necessarily constitute prior art.
[0003] Metallic molybdenum (Mo) has the advantages of high melting point (2617°C), high strength, and corrosion resistance, and is an important candidate material for high-temperature cladding of special nuclear reactor fuel elements at or above 1200°C. However, metallic molybdenum is very easy to oxidize in an oxidizing atmosphere above 400°C, and molybdenum oxide begins to volatilize severely at 700°C, which limits its use as a high-temperature structural material.
[0004] At present, the method of preparing a protective coating on the surface of molybdenum is usually used to improve its high temperature oxidation resistance. 2 However, the high temperature oxidation resistance of the protective coatings currently prepared is not ideal. Summary of the invention
[0005] A brief overview of the present application is provided below in order to provide a basic understanding of certain aspects of the present application. It should be understood that this overview is not an exhaustive overview of the present application. It is not intended to identify the key or important parts of the present application, nor is it intended to limit the scope of the present application. Its purpose is merely to present certain concepts in a simplified form as a prelude to a more detailed description discussed later.
[0006] The embodiment of the present application provides a method for preparing a surface coating of a molybdenum substrate, comprising: S1, obtaining silicon powder and a molybdenum substrate; S2, coating the molybdenum substrate with silicon powder and heating the molybdenum substrate to obtain a surface coating of MoSi 2 Molybdenum substrate of transition layer; S3, obtain mixed powder including carbon powder, silicon powder, chromium powder and titanium powder; S4, form MoSi 2 The molybdenum substrate of the transition layer is coated with mixed powder and heated to obtain MoSi 2 (Mo,Cr,Ti)Si is formed outside the transition layer 2 Molybdenum substrate for composite coating.
[0007] The inventors of the present application have found that the prepared single MoSi 2 The oxidation life of the coating at high temperature (e.g. 1400°C) is only 40h, and the mass change per unit area is -41g / m 2 , the mass change rate is -0.80%. 2It is difficult to completely avoid the presence of many pores and longitudinal cracks in the coating, so it is difficult to effectively prevent the diffusion of oxygen into the molybdenum substrate, which leads to the oxidation resistance life in air at 1400°C still far from meeting the requirements. 2 The transition layer and then the MoSi 2 (Mo,Cr,Ti)Si is formed outside the transition layer 2 Composite coating can block or heal cracks, thereby increasing the diffusion resistance of oxygen to improve the high-temperature oxidation resistance and high-temperature oxidation life of the molybdenum matrix.
[0008] These and other advantages of the present application will become more apparent through the following detailed description of the preferred embodiments of the present application in conjunction with the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0009] In order to further illustrate the above and other advantages and features of the present application, the specific embodiments of the present application are further described in detail below in conjunction with the accompanying drawings. The accompanying drawings together with the following detailed description are included in this specification and form a part of this specification. Elements with the same function and structure are represented by the same reference numerals. It should be understood that these drawings only describe typical examples of the present application and should not be regarded as limiting the scope of the present application.
[0010] Figure 1 is a schematic flow chart of a method for preparing a surface coating of a molybdenum substrate according to an embodiment of the present application;
[0011] Figure 2 According to one embodiment of the present application, (Mo, Cr, Ti)Si 2 The strength of the composite coating before and after oxidation varies with the crystal diffraction angle in phase structure analysis;
[0012] Figure 3 According to one embodiment of the present application, MoSi 2 (Mo,Cr,Ti)Si is formed outside the transition layer 2 Schematic diagram of the molybdenum substrate of the composite coating;
[0013] Figure 4 yes Figure 1 MoSi 2 (Mo,Cr,Ti)Si is formed outside the transition layer 2 Schematic diagram of the molybdenum substrate of the composite coating after oxidation;
[0014] Figure 5 According to an embodiment of the present application, (Mo, Cr, Ti)Si at different temperatures 2 Curve of the mass per unit area of the composite coating changing with oxidation time;
[0015] Figure 6 According to one embodiment of the present application, (Mo, Cr, Ti)Si 2 The curve of mass change rate of the composite coating versus temperature and the endothermic and exothermic curves during the reaction process.
[0016] It should be noted that the drawings are not necessarily drawn to scale, but are merely shown in a schematic manner that does not affect the reader's understanding. DETAILED DESCRIPTION
[0017] Exemplary embodiments of the present application will be described below in conjunction with the accompanying drawings. For the sake of clarity and conciseness, not all features of the actual implementation are described in the specification. However, it should be understood that many implementation-specific decisions must be made in the process of developing any such actual implementation in order to achieve the developer's specific goals, such as meeting those constraints related to the system and business, and these constraints may vary from implementation to implementation. In addition, it should be understood that although the development work may be very complex and time-consuming, it is only a routine task for those skilled in the art who benefit from the content of this application.
[0018] It is also necessary to explain here that, in order to avoid obscuring the present application due to unnecessary details, only the device structure and / or processing steps closely related to the scheme according to the present application are shown in the accompanying drawings, while other details that are not very relevant to the present application are omitted.
[0019] It should be noted that, unless otherwise defined, the technical terms or scientific terms used in this application should have the common meanings understood by persons with ordinary skills in the field to which this application belongs.
[0020] In the description of the embodiments of the present application, “plurality” means at least two, such as two, three, etc., unless otherwise clearly and specifically defined.
[0021] In the related art, MoSi on the surface of metal molybdenum 2 The coating is brittle at low temperatures of 400-700°C, which can easily lead to accelerated oxidation and powdering of the molybdenum matrix. 2 The coating is mostly composed of an outer layer of MoSi 2 and inner Mo 5 Si 3 However, due to the MoSi 2 The thermal expansion coefficients of the coating and the metal molybdenum substrate do not match, and the Mo generated by the oxidation reaction 5 Si 3The phase will also cause the volume expansion of the coating, especially under the oxidation conditions of hot and cold cycles, there is a large residual stress, which will inevitably cause cracks in the coating or even peeling off, losing the protective effect on the molybdenum substrate. 2 The coating's resistance to high-temperature oxidation is not excellent, and it is also difficult to improve its high-temperature oxidation life.
[0022] In view of the above technical problems, the embodiments of the present application provide a method for preparing a surface coating of a molybdenum substrate, such as Figure 1 As shown, Figure 1 It is a schematic flow chart of a method for preparing a surface coating of a molybdenum substrate according to an embodiment of the present application. The preparation method may at least include the following steps S1 to S4.
[0023] S1. Obtain silicon powder and molybdenum matrix.
[0024] S2, the molybdenum substrate is coated with silicon powder and heated to obtain a surface-formed MoSi 2 Molybdenum matrix of the transition layer.
[0025] S3. Obtaining a mixed powder including carbon powder, silicon powder, chromium powder, and titanium powder.
[0026] S4, forming MoSi on the surface 2 The molybdenum substrate of the transition layer is coated with mixed powder and heated to obtain MoSi 2 (Mo,Cr,Ti)Si is formed outside the transition layer 2 Molybdenum substrate for composite coating.
[0027] The inventors of the present application have found that the prepared single MoSi 2 The oxidation life of the coating at high temperature (e.g. 1400°C) is only 40h, and the mass change per unit area is -41g / m 2 , the mass change rate is -0.80%. 2 It is difficult to completely avoid the presence of many pores and longitudinal cracks in the coating, so it is difficult to effectively prevent the diffusion of oxygen into the molybdenum substrate, which leads to the oxidation resistance life in air at 1400°C still far from meeting the requirements. 2 The transition layer and then the MoSi 2 (Mo,Cr,Ti)Si is formed outside the transition layer 2 Composite coating can block or heal cracks, thereby increasing the diffusion resistance of oxygen to improve the high-temperature oxidation resistance and high-temperature oxidation life of the molybdenum matrix.
[0028] In some embodiments, in step S1, the average particle size of silicon (Si) powder can be less than or equal to 3 μm to increase the contact area between Si powder and molybdenum powder and the reaction activity in the subsequent coating process, thereby facilitating the full reaction.
[0029] In some embodiments, the metal molybdenum may be pretreated to remove the transition layer on its surface, and then the pretreated metal molybdenum may be polished and ground to obtain the Mo matrix in step S1.
[0030] In some embodiments, step S4 may include: S41, forming MoSi on the surface 2 The molybdenum matrix of the transition layer is coated with mixed powder, and is heated to a first preset temperature and maintained in a vacuum or inert atmosphere; S42, the heating is stopped after waiting for a first preset time, and the cooling is performed to form a MoSi 2 (Mo,Cr,Ti)Si is formed outside the transition layer 2 Composite coating; S43, MoSi 2 (Mo,Cr,Ti)Si is formed outside the transition layer 2 The molybdenum substrate of the composite coating is ultrasonically cleaned and dried at a second preset temperature; wherein the second preset temperature is lower than the first preset temperature.
[0031] The method provided in the embodiment of the present application forms a MoSi film on the surface coated with the mixed powder under vacuum or inert atmosphere. 2 The molybdenum substrate of the transition layer is heated to a first preset temperature to avoid oxidation of the metal elements to ensure that (Mo, Cr, Ti)Si 2 Preparation effect of composite coating; 2 (Mo,Cr,Ti)Si is formed outside the transition layer 2 The molybdenum substrate of the composite coating is ultrasonically cleaned to remove (Mo, Cr, Ti) Si 2 The powder attached to the surface of the composite coating avoids damage to the composite coating; drying at the second preset temperature can ensure that Si has good shrinkage characteristics and further ensure the antioxidant performance of the composite coating; at the same time, in the embodiment of the present application, the mixed powder is used to coat MoSi 2 The transition layer is MoSi 2 (Mo,Cr,Ti)Si is formed outside the transition layer 2 The composite coating can be applied to the preparation of inner and outer surface coatings of products with deep inner holes.
[0032] In some embodiments, in step S41, the surface may be formed into MoSi 2The molybdenum matrix of the transition layer is embedded in the mixed powder infiltrant and loaded into a boat, which is appropriately compacted and covered; then placed in a heating device; the heating device is then evacuated, and a high-purity inert gas is introduced, and the temperature is heated to a first preset temperature and maintained. Exemplarily, the heating device may be a tube furnace. The inert gas may be argon with a purity of not less than 99%.
[0033] In some embodiments, in step S42, the heating may be stopped and the furnace may be cooled.
[0034] In some embodiments, the first preset temperature may be in the range of 1000-1400 degrees Celsius; the first preset time may be in the range of 2-15 hours to ensure that Si can be fully diffused.
[0035] In some embodiments, the second preset temperature may be equal to 60°C.
[0036] In some embodiments, in step S43, ultrasonic cleaning may include: obtaining an ultrasonic cleaning solution including ultrasonic cleaning particles; 2 (Mo,Cr,Ti)Si is formed outside the transition layer 2 The molybdenum substrate of the composite coating was ultrasonically cleaned.
[0037] The embodiments of the present application utilize an ultrasonic cleaning solution including ultrasonic cleaning particles to perform ultrasonic cleaning, which can improve the cleaning effect of ultrasonic cleaning.
[0038] In some embodiments, the ultrasonic cleaning particles may be Si particles.
[0039] In some embodiments, in step S43, drying at the second preset temperature may include: drying the MoSi after ultrasonic cleaning at a temperature of 40-60 degrees Celsius. 2 (Mo,Cr,Ti)Si is formed outside the transition layer 2 The molybdenum substrate of the composite coating is dried and waited for 2-6 hours, wherein the second preset temperature is within the range of 40-60 degrees Celsius.
[0040] In some embodiments, after step S4, the preparation method may further include: S5, 2 (Mo,Cr,Ti)Si is formed outside the transition layer 2 The molybdenum substrate of the composite coating is heated to a third preset temperature for pre-oxidation.
[0041] The embodiment of the present application is to 2 (Mo,Cr,Ti)Si is formed outside the transition layer 2 The molybdenum substrate of the composite coating is pre-oxidized to form a (Mo,Cr,Ti)Si 2SiO is pre-generated on the surface of the composite coating 2 , to eliminate (Mo,Cr,Ti)Si 2 The residual stress in the composite coating is reduced and is conducive to the early healing of most cracks.
[0042] In some embodiments, step S5 may include: heating the MoSi 2 (Mo,Cr,Ti)Si is formed outside the transition layer 2 The molybdenum substrate of the composite coating is heated and waited for 2-6 hours, wherein the third preset temperature is in the range of 1000-1200 degrees Celsius.
[0043] In some embodiments, step S2 may include: S21, coating the molybdenum substrate with silicon powder, heating to a fourth preset temperature and maintaining the temperature under an inert atmosphere; S22, stopping heating after waiting for a second preset time to form MoSi on the surface of the molybdenum substrate. 2 Transition layer.
[0044] In the embodiment of the present application, the molybdenum substrate coated with Si powder is heated to a fourth preset temperature and maintained for a second preset time under an inert atmosphere, so that the MoSi formed on the surface of the molybdenum substrate is 2 The transition layer has good density; and in the embodiment of the present application, Si powder is used to coat the Mo matrix to prepare MoSi 2 The transition layer can be used for the preparation of inner and outer surface coatings of products with deep inner holes.
[0045] In some embodiments, MoSi can be prepared by embedding method. 2 The fourth preset temperature may be in the range of 1000-1300° C., and the second preset time may be in the range of 2-15 hours.
[0046] In some embodiments, step S21 and step S22 may be performed in an argon environment with a gas purity of not less than 99%.
[0047] In some embodiments, step S3 may include: S31, obtaining carbon powder, silicon powder, chromium powder, titanium powder and anhydrous ethanol; S32, mixing the carbon powder, silicon powder, chromium powder, titanium powder and anhydrous ethanol to form a mixture; S33, vacuum drying the mixture to obtain a mixed powder. The method provided in the embodiment of the present application can quickly and conveniently obtain a mixed powder with a good mixing effect.
[0048] In some embodiments, the mixture may be formed by mixing and ball-milling high-purity carbon powder (graphite powder), Si powder, Cr powder, Ti powder and anhydrous ethanol.
[0049] In some embodiments, in the mixture, the mass ratio of carbon powder is 0-10%, the mass ratio of silicon powder is 30-70%, the mass ratio of chromium powder is 5-30%, and the mass ratio of titanium powder is 5-30%. The mass ratio in the embodiments of the present application can ensure that the infiltration reaction can be fully carried out while reducing the influence of impurities brought by excess products on the purity of the finally obtained mixture.
[0050] In some embodiments, the preparation method provided in the embodiments of the present application does not require the use of complex plasma spraying and other processes and equipment to prepare the coating, but instead uses a convenient powder embedding process and a commonly used furnace to prepare the coating, which can be applied to the preparation of inner and outer surface coatings of products with deep inner holes. Figure 2 and Figure 4 As shown, Figure 2 According to one embodiment of the present application, (Mo, Cr, Ti)Si 2 The strength of the composite coating before and after oxidation varies with the crystal diffraction angle (2θ) in phase structure analysis. Figure 4 yes Figure 1 MoSi 2 (Mo,Cr,Ti)Si is formed outside the transition layer 2 Schematic diagram of the molybdenum substrate of the composite coating after oxidation, using a two-step embedding method, preferably C-Si-Cr-Ti mixed powder and embedding reaction process parameters of the embodiment of the present application, a three-layer microstructure (Mo, Cr, Ti)Si with a total thickness of 165 μm can be obtained 2 The composite coating can effectively prevent oxygen from diffusing into the molybdenum matrix. Figure 3 According to one embodiment of the present application, MoSi 2 (Mo,Cr,Ti)Si is formed outside the transition layer 2 Schematic diagram of the molybdenum substrate of the composite coating, see Figure 3 , the inner side of the composite coating is Mo 5 Si 3 layer, with a thickness of 28μm; the middle layer is (Mo,Cr,Ti)Si 2 layer, with a thickness of 117μm; the outermost layer is a Si, Al, Ti, Ca compound layer, with a thickness of 20μm; Figure 4 ,(Mo,Cr,Ti)Si 2 After oxidation at 1400℃ for 100h, the thickness of the composite coating can be changed to 220μm.
[0051] In some embodiments, Figure 5 and Figure 6 As shown, Figure 5 The curves a, b, and c shown are (Mo, Cr, Ti)Si 2Curves showing the variation of unit area mass of composite coating with oxidation time at 1400℃, 1300℃ and 1200℃; Figure 6 The curve d shown is (Mo,Cr,Ti)Si 2 The mass change rate of the composite coating changes with temperature (TG curve), and curve e is the endothermic and exothermic curves (DSC curve) during the reaction process. (Mo, Cr, Ti) Si prepared by the method provided in the embodiment of the present application 2 The composite coating remained intact after being oxidized in air at 1400℃ for 100h, and the mass change per unit area was +9.12g / m 2 The mass change rate is +0.19%, and there is no oxidation weight loss phenomenon, even when oxidized at 1500℃ for a short time.
[0052] In some embodiments, (Mo, Cr, Ti)Si prepared by the method provided in the embodiments of the present application 2 After the composite coating was oxidized at 1400℃ for 100h, it was mainly composed of α-SiO 2 Cr 2 Mo 3 O 12 、SiO 2 、Mo 5 Si 3 、MoSi 2 Composition, of which α-SiO 2 and Cr 2 Mo 3 O 12 The oxides of Cr, Ti and other elements distributed in the outermost layer may be related to SiO 2 The reaction forms a dense complex silicate oxide, molten SiO 2 It will penetrate into the cracks and fill them, which can improve the self-healing ability of the oxide film and prevent oxygen from diffusing into the molybdenum matrix. 2 The composite coating contains three layers of microstructure: SiO 2 The film is dense and can fill cracks. The interface between the coating and the Mo substrate is zigzag and cross-bonded, making it difficult to peel off, which makes the coating have excellent antioxidant properties at a high temperature of 1400°C.
[0053] The following is a specific example to further illustrate the process of preparing a molybdenum substrate surface coating using the method in this application.
[0054] Example 1
[0055] First, in an inert atmosphere, MoSi was prepared by embedding Si powder on the surface of a pretreated, ground, and polished Mo substrate. 2Transition layer, reaction temperature is 1000°C, holding time is 15 hours, inert atmosphere is 99.99% high purity argon.
[0056] Second, high-purity graphite powder, Si powder, Cr powder, Ti powder and anhydrous ethanol are mixed and ball-milled, and then vacuum-dried at 60° C. for later use.
[0057] Third, the surface is formed into MoSi 2 The Mo matrix of the transition layer is embedded in a mixed powder with a mass ratio of 2% C-50% Si-28% Cr-20% Ti, packed in a boat, compacted appropriately and covered, and then placed in a tube furnace.
[0058] Fourth, the tube furnace is first evacuated, and then high-purity argon is introduced, heated to 1200℃ and kept warm for 15 hours for reaction, and then cooled with the furnace and the MoSi 2 Transition layer formation (Mo,Cr,Ti)Si 2 Composite coating.
[0059] Fifth, the prepared (Mo,Cr,Ti)Si 2 The composite coating was heated to 1200°C in air and then pre-oxidized for 4 hours.
[0060] Example 2
[0061] First, in an inert atmosphere, MoSi was prepared by embedding Si powder on the surface of a pretreated, ground, and polished Mo substrate. 2 Transition layer, reaction temperature is 1200°C, holding time is 8 hours, inert atmosphere is 99.99% high purity argon.
[0062] Second, high-purity graphite powder, Si powder, Cr powder, Ti powder and anhydrous ethanol are mixed and ball-milled, and then vacuum-dried at 60° C. for later use.
[0063] Third, the surface is formed into MoSi 2 The Mo matrix of the transition layer is embedded in a mixed powder with a mass ratio of 5% C-60% Si-20% Cr-15% Ti, packed in a boat, properly compacted and covered, and then placed in a tube furnace.
[0064] Fourth, evacuate the tube furnace, then introduce high-purity argon gas, heat to 1200℃ and keep warm for 12 hours to react, and then cool down the furnace and then 2 Transition layer formation (Mo,Cr,Ti)Si 2 Composite coating.
[0065] Fifth, the prepared (Mo,Cr,Ti)Si 2 The composite coating was heated to 1200°C in air and then pre-oxidized for 4 hours.
[0066] Example 3
[0067] First, in an inert atmosphere, MoSi was prepared by embedding Si powder on the surface of a pretreated, ground, and polished Mo substrate. 2 Transition layer, reaction temperature is 1300°C, holding time is 5 hours, inert atmosphere is 99.99% high purity argon.
[0068] Second, high-purity graphite powder, Si powder, Cr powder, Ti powder and anhydrous ethanol are mixed and ball-milled, and then vacuum-dried at 60° C. for later use.
[0069] Third, the surface is formed into MoSi 2 The Mo matrix of the transition layer is embedded in a mixed powder with a mass ratio of 10% C-40% Si-20% Cr-30% Ti, packed in a boat, properly compacted and covered, and then placed in a tube furnace.
[0070] Fourth, evacuate the tube furnace, then introduce high-purity argon gas, heat to 1300℃ and keep warm for 8 hours to react, and then cool down the furnace and then 2 Transition layer formation (Mo,Cr,Ti)Si 2 Composite coating.
[0071] Fifth, the prepared (Mo,Cr,Ti)Si 2 The composite coating was heated to 1100°C in air and then pre-oxidized for 3 hours.
[0072] Regarding the embodiments of the present application, it should also be noted that, in the absence of conflict, the embodiments of the present application and the features therein can be combined with each other to obtain new embodiments.
[0073] The above description is only a specific implementation manner of the present application, but the protection scope of the present application is not limited thereto. The protection scope of the present application shall be based on the protection scope of the claims.
Claims
1. A method for preparing a molybdenum substrate surface coating, characterized in that: include: S1, obtaining silicon powder and molybdenum matrix; S2, coating the molybdenum substrate with the silicon powder and heating the substrate to obtain the molybdenum substrate with a MoSi2 transition layer formed on the surface; S3, obtaining a mixed powder including carbon powder, silicon powder, chromium powder, and titanium powder; S4. The molybdenum substrate with the MoSi2 transition layer formed on the surface is coated with the mixed powder and heated to obtain the molybdenum substrate with a (Mo, Cr, Ti)Si2 composite coating formed outside the MoSi2 transition layer.
2. The preparation method according to claim 1, characterized in that: The S4 step includes: S41, the molybdenum substrate with the MoSi2 transition layer formed on the surface is coated with the mixed powder, and heated to a first preset temperature and then maintained under vacuum or inert atmosphere; S42, stopping heating after waiting for a first preset time, and cooling to form a (Mo, Cr, Ti)Si2 composite coating outside the MoSi2 transition layer; S43. Ultrasonic cleaning is performed on the molybdenum substrate having the (Mo, Cr, Ti)Si2 composite coating formed outside the MoSi2 transition layer, and drying is performed at a second preset temperature; wherein the second preset temperature is lower than the first preset temperature.
3. The preparation method according to claim 2, characterized in that: The first preset temperature is in the range of 1000-1400 degrees Celsius; the first preset time is in the range of 2-15 hours.
4. The preparation method according to claim 2 or 3, characterized in that: In the step S43, the ultrasonic cleaning includes: obtaining an ultrasonic cleaning solution including ultrasonic cleaning particles; The ultrasonic cleaning liquid is used to ultrasonically clean the molybdenum substrate with a (Mo, Cr, Ti)Si2 composite coating formed outside the MoSi2 transition layer.
5. The preparation method according to claim 2 or 3, characterized in that: In the step S43, the drying at the second preset temperature includes: The molybdenum substrate with the (Mo, Cr, Ti)Si2 composite coating formed outside the MoSi2 transition layer after ultrasonic cleaning is dried under a temperature condition of 40-60 degrees Celsius, and waited for 2-6 hours, wherein the second preset temperature is within the range of 40-60 degrees Celsius.
6. The preparation method according to claim 1, characterized in that: After the step S4, the preparation method further comprises: S5. Heating the molybdenum substrate having a (Mo, Cr, Ti)Si2 composite coating formed outside the MoSi2 transition layer to a third preset temperature for pre-oxidation.
7. The preparation method according to claim 6, characterized in that: The S5 step includes: The molybdenum substrate with the (Mo, Cr, Ti)Si2 composite coating formed outside the MoSi2 transition layer is heated at a temperature of 1000-1200 degrees Celsius and waited for 2-6 hours, wherein the third preset temperature is within the range of 1000-1200 degrees Celsius.
8. The preparation method according to claim 1, characterized in that: The S2 step includes: S21, coating the molybdenum substrate with the silicon powder, heating the substrate to a fourth preset temperature and maintaining the temperature under an inert atmosphere; S22, stopping heating after waiting for a second preset time to form the MoSi2 transition layer on the surface of the molybdenum substrate.
9. The preparation method according to claim 1, characterized in that: The S3 step includes: S31, obtaining the carbon powder, the silicon powder, the chromium powder, the titanium powder and anhydrous ethanol; S32, mixing the carbon powder, the silicon powder, the chromium powder, the titanium powder and the anhydrous ethanol to form a mixture; S33, vacuum drying the mixture to obtain the mixed powder.
10. The preparation method according to claim 9, characterized in that: In the mixture, the mass ratio of the carbon powder is 0-10%, the mass ratio of the silicon powder is 30-70%, the mass ratio of the chromium powder is 5-30%, and the mass ratio of the titanium powder is 5-30%.